Venetoclax combines synergistically with FLT3 inhibition to effectively target leukemic cells in FLT3-ITD+ acute myeloid leukemia models - Singh Mali, Raghuveer; Zhang, Qi; DeFilippis, Rosa Anna; Cavazos, Antonio; Kuruvilla, Vinitha Mary; Raman, Jayant; Mody, Vidhi; Choo, Edna F; Dail, Monique; Shah, Neil P; Konopleva, Marina; Sampath, Deepak; et al. (Haematologica (Roma), 2021)
FLT3 internal tandem duplication (FLT3-ITD) mutations account for ~25% of adult acute myeloid leukemia cases and are associated with poor prognosis. Venetoclax, a selective BCL-2 inhibitor, has limited monotherapy activity in relapsed/refractory acute myeloid leukemia with no responses observed in a small subset of FLT3-ITD+ patients. Further, FLT3-ITD mutations emerged at relapse following venetoclax monotherapy and combination therapy suggesting a potential mechanism of resistance. Therefore, we investigated the convergence of FLT3-ITD signaling on the BCL-2 family proteins and determined combination activity of venetoclax and FLT3-ITD inhibition in preclinical models. In vivo, venetoclax combined with quizartinib, a potent FLT3 inhibitor, showed greater anti-tumor efficacy and prolonged survival compared to monotherapies. In a patient-derived FLT3-ITD+ xenograft model, cotreatment with venetoclax and quizartinib at clinically relevant doses had greater anti-tumor activity in the tumor microenvironment compared to quizartinib or venetoclax alone. Use of selective BCL-2 family inhibitors further identified a role for BCL-2, BCL-XL and MCL-1 in mediating survival in FLT3-ITD+ cells in vivo and highlighted the need to target all three proteins for greatest anti-tumor activity. Assessment of these combinations in vitro revealed synergistic combination activity for quizartinib and venetoclax but not for quizartinib combined with BCL-XL or MCL-1 inhibition. FLT3-ITD inhibition was shown to indirectly target both BCL-XL and MCL-1 through modulation of protein expression, thereby priming cells toward BCL-2 dependence for survival. These data demonstrate that FLT3-ITD inhibition combined with venetoclax has impressive anti-tumor activity in FLT3-ITD+ acute myeloid leukemia preclinical models and provides strong mechanistic rational for clinical studies.